VA-ECOM assisted percutaneous mechanical thrombectomy treatment high-risk pulmonary embolism - Zhenhang Zhou; Zhenhang Zhou; Zhenhang Zhou; Yaoyang Zhong; Yaoyang Zhong; Yaoyang Zhong; Jianbo Hu; Jianbo Hu; Jianbo Hu; Zhonghua Wu; Zhonghua Wu; Zhonghua Wu; et al. (Frontiers in Cardiovascular Medicine)
BackgroundPercutaneous mechanical thrombectomy (PMT) is increasingly used in the treatment of intermediate and high-risk acute pulmonary embolism (PE), and the treatment of high-risk PE with the aid of veno-arterial extracorporeal membrane oxygenation (VA-ECMO) has also been reported. However, there are few reports of VA-ECOM-assisted PMT in the treatment of high-risk PE. The purpose of this study is to summarize the data of 11 patients with high-risk PE treated with VA-ECMO assisted PMT, and propose feasible treatment methods for such patients.MethodsThis multicenter retrospective study included patients with acute high-risk PE who were treated with VA-ECMO-assisted PMT from January 2021 to June 2024. The analysis focused on the right/left ventricle ratio, biomarkers, and pulmonary artery pressure before and after the VA-ECMO-assisted PMT treatment.ResultsAll 11 high-risk PE patients suffered cardiac arrest before treatment, computered tomograhy pulmonary angiography (CTPA) confirmed the diagnosis of PE, and all patients received VA-ECMO-assisted PMT therapy. The median age of the 11 patients was 54 years (range 18–72), the median duration of ECMO was 4.48 days (range 1.04–18.02), and the mean hospitalization time was 21 days (range 14–112). All patients received percutaneous thrombectomy, achieving a 100% technical success rate. The mortality rate was 27.3% during the 90-day follow-up. The 12-month mortality rate was 36.4%.ConclusionVA-ECMO-assisted PMT technology can rapidly improve pulmonary hemodynamics while maintaining stable blood flow, thereby reducing in-hospital mortality in high-risk patients with pulmonary embolism complicated by cardiac arrest.